Navigating the Monetary Sanctions Maze: Understanding and Confusion Among Criminal Legal Debtors. (February 2021) - Spencer-Suarez, Kimberly; Martin, Karin D.
Monetary sanctions in the criminal legal system are legally and procedurally complex. If not paid in a timely manner, a single conviction can result in multiple legal financial obligations, varying in kind, payment procedure, and consequences. This study examines how, and the extent to which, criminal legal debtors understand monetary sanctions. Based on interviews with 60 individuals who owed criminal legal debt in New York, we propose a typology of debtor understanding. Proximal understanding pertains to individual, case-level factors and is instrumentally oriented. Distal understanding concerns system-level matters and is oriented toward normativity and fairness. We examine how debtors develop each type of understanding, how these dimensions interact, and the implications of debtor understanding for compliance behavior.